Chatbot Development through Design Thinking Techniques: An Exploratory Study from Students’ Perspective - Villa, João Emilio Antonio; Vilela, Ricardo Ferreira; Valle, Pedro Henrique; Silva, Williamson (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2025: Anais do XXIV Simpósio Brasileiro de Qualidade de Software, 2025)
Text-based conversational agents (chatbots) have become central interfaces in modern interactive systems, widely used in contexts ranging from customer support to educational environments, personal assistants, and healthcare systems. However, developing chatbots is a challenging process, as it requires identifying requirements and understanding users’ perspectives on these systems. In this context, Design Thinking (DT) has emerged as a promising approach for promoting creativity, empathy, and innovation in developing solutions centered on the needs of end-users. Therefore, it is necessary to incorporate DT into the Software Engineering curriculum to provide students with the skills needed to develop chatbots effectively. In this sense, this paper presents an exploratory study conducted with 13 undergraduate students aiming to investigate the DT cycles, with an emphasis on techniques that promote empathy in the conception, design, and evaluation of chatbots. The study involved participants in practical immersion activities, utilizing several methods to understand the context of use and the needs of users. We collected the data through diaries and questionnaires answered by the participants. The results show that participants were able to identify latent needs, generate more empathetic and contextually relevant proposals, and engage more actively in the design process.